The price (and costs) of macroeconomic stability in Peru: Some lessons on the implications of FDI-driven growth - Bibi, Samuele (2023)
In the period 2000-2019, Peru enjoyed sustained GDP growth and a long period of macroeconomic stability; as a result, poverty was reduced markedly in comparison to the 1980s and early 1990s, when the country faced severe recessions and hyperinflation. This positive economic performance coincided with the implementation of a mainstream macroeconomic framework which, alongside favourable external conditions, allowed for continuous external financing of current account deficits, mainly through foreign direct investment (FDI). Against the background of current debates regarding the resurgence of debt crises and the advocacy of FDI as a way to avoid such crises, this article uses balance of payments and international investment position statistics to assess whether Peru's acquired macroeconomic stability can be deemed sustainable. Drawing on the contributions of the Latin American structuralist school and more recent analyses that have raised concerns, the article shows that Peru's external position has taken on a Ponzi profile, casting doubt on the idea that FDI is a superior way of external financing compared to external debt. It concludes with a discussion of the social and environmental implications of Peru's widely praised macroeconomic framework, highlighting the limits that peripheral economies face when their growth relies excessively on external financing.